The experiment editor: supporting inquiry-based learning with virtual labs. (8th March 2017) - Galan, D; Heradio, R; de la Torre, L; Dormido, S; Esquembre, F
Abstract: Inquiry-based learning is a pedagogical approach where students are motivated to pose their own questions when facing problems or scenarios. In physics learning, students are turned into scientists who carry out experiments, collect and analyze data, formulate and evaluate hypotheses, and so on. Lab experimentation is essential for inquiry-based learning, yet there is a drawback with traditional hands-on labs in the high costs associated with equipment, space, and maintenance staff. Virtual laboratories are helpful to reduce these costs. This paper enriches the virtual lab ecosystem by providing an integrated environment to automate experimentation tasks. In particular, our environment supports: (i) scripting and running experiments on virtual labs, and (ii) collecting and analyzing data from the experiments. The current implementation of our environment supports virtual labs created with the authoring tool Easy Java/Javascript Simulations. Since there are public repositories with hundreds of freely available labs created with this tool, the potential applicability to our environment is considerable.